Investigation on surface morphology and crystalline phase deformation of Al80Li5Mg5Zn5Cu5 high-entropy alloy by ultra-precision cutting. (15th January 2020) - Huang, Zhiyuan; Dai, Yuqi; Li, Zhen; Zhang, Guoqing; Chang, Chuntao; Ma, Jiang
Abstract: The materials with high precision，easy machining and excellent micro-machinability are considered significant on the fabrication of precision components, the outstanding comprehensive properties of Al80 Li5 Mg5 Zn5 Cu5 high-entropy alloy just meet these requirements. Firstly, our study found that the feed rate parameters have the greatest influence on the surface quality of material, and the surface roughness can reach 6 nm at the lowest level. After ultra-precision cutting the material, we found that the cutting process of high-entropy alloy has no obvious damage to the cutting tools and two distinct phases (FCC α-Al phase and Al/Al2 Cu/MgZn2 quaternary eutectics phase) were formed on the finished surface under the observation of scanning electron microscopy. By comparing the size of two phases and the morphology of undeformed chips cut by diamond tool and polycrystalline cubic boron nitride (PCBN) tool, the material surface cut by PCBN tool was subjected to greater extrusion force and friction during machining, leading to more remarkable increase in surface microhardness. Graphical abstract: Unlabelled Image Highlights: The mechanism of ultra-precision machining of HEAs has been deeply studied. The effects of spindle speed, feed rate and depth of cut on high-entropy alloy surface quality have been investigated for the first time. Two distinct phases with different deformation homogeneous distribute on the HEA surface by ultra-precision machining.